Enterprise information systems and the digitalization of business functions - Tavana, Madjid (IGI Global, 2017)
"[This book] is a key resource on the latest advances and research for a digital agenda in the business world. Highlighting multidisciplinary studies on data modeling, information systems, and customer relationship management, this publication is an ideal reference source for professionals, researchers, managers, consultants, and university students interested in emerging developments for business process management"- Resumé vydavatel
Keywords: podnikové informační systémy; management information systems; kolektivní monografie; elektronické knihy; collective monographs; electronic books